Talk from the top down - Cameron, D (Elsevier, 2008)
This article considers the phenomenon of 'top-down talk' - interaction in institutional settings where the use of language is highly regulated and standardized, so that many aspects of interaction are in effect designed not by the participants themselves, but by superordinate agents such as managers and consultants. Focusing on data from customer service interactions in UK call centres, the article discusses both the practical problems top-down talk poses for those directly involved in it, and its theoretical implications for microanalytic approaches such as conversation analysis (CA).